Determination of Settlement for Beam on Elastic Foundation by ETABS Software - Harba, Ibrahim S. I.; Rubaie, Oday S. B. AL (Al-Nahrain Journal for Engineering Sciences, 2018)
In this study a numerical examples and solutions has been obtained by using three system of beam resting on elastic foundation (BOEF) which was adopted previously by three different engineering software. The first part of this paper was related to verify the model of (BOEF) by using ETABS2015 by make a comparison with previous results by determination the maximum settlements at the mid of span which show a good agreement between ETABS2015 and other results, where the total differences was vary from 2.13 % to 3.27%. . The second part of this study was highlighted on the settlement of BOEF with different parametric study (beam thickness, soil subgrade reaction(KS) and the load location), case (1) was selected for this goal. In this paper it is found that the differential settlement along the beam are decrease as increasing in the beam stiffness in addition to possibility to obtain uplift (positive settlement ) for some type of changing in the load location specially for higher thick beam . It was noticed that the settlement are increased significantly as reducing in the (KS). Finally this study show a different form of deflection by combination two of parametric study.